RESPON IMUN SELULER PADA PERIODONTITIS DIABETIKA - , Ahmad Syaify, drg.Sp.Perio. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The severity of diaberic periodontitis was strongly thought caused by immune response disorder, especially by decreasing functions of monocytes and neutrophiles. Calprotectin is cytosolic protein that was only produced by neutrophiles and monoctyes. It was also existed in serum and gingival crevicular fluid. The aims of this study was to determine the role of innate immune response in diabetic periodontitis on calprotectin level in terms of gingival crevicular fluid, serum, monocytes and neutrophiles and the expression MRP8/14 on both these phagocytic cells, and their phagocytosis function. Observational research with cross sectional approach was taken to assess levels of calprotectin in gingival crevicular fluid serum, monocytes and neutrophils of diabetic patients with periodontitis using ELISA technique. Quasi experimental research was conducted to study the response of monocytes and neutrophils in MRP8/MRP14 mRNA expression after both phagocytic cells stimulated with lipopolysaccharide (LPS) E. coli bacteria. Detection of calprotectin expression of this genetic code using RT-PCR technique, was then followed by electrophoresis, and the density of PCR bands with thin layer chromatography (TLC) was analyzed. Test of phagocytosis activity of monocytes and neutrophils was done using latex particles and phagocytosis index was resumed. The results showed an increased calprotectin levels in uncontrolled diabetic patients with periodontitis, both in gingival crevicular fluid, serum, and peripheral blood monocytes and neutrophils. Statistical analysis using Oneway ANOVA showed significant differences (p<0.05) between calprotectin level of periodontitis patients with uncontrolled type 2 diabetes, those with controlled type 2 diabetes, and without diabetes. Meanwhile, test on MRP8/MRP14 mRNA expression of monocytes and neutrophils provided the highest expression in the periodontitis group with uncontrolled type 2 diabetes and lowest expression in non-diabetic periodontitis, which was statistically significant difference (p <0.05). While phagocytosis index indicated the opposite tendency, namely in periodontitis patients with uncontrolled type 2 diabetes phagocytic index of monocytes and neutrophils were precisely lowest compared to periodontitis in controlled type 2 diabetes, and non-diabetic periodontitis with highest phagocytosis index. Result of Oneway ANOVA showed that differences in phagocytic index was significantly different (p <0.05). The conclusion of the research are level calprotetctin and MRP8/14 mRNA expression increased on periodontitis patients with type 2 DM. On the other hand, the phagocytosis activity decreased on those patients. The highest level of calprotectin and MRP8/14 expression was on periodontitis patients with type 2 DM. It was suggested that level of calprotectin and MRP8/14 expression have a role in the regulation of severity diabetic periodontitis.